STUDI PERBANDINGAN PENGARUH TEKNIK PETA KONSEP DAN TEKNIK GAMING TERHADAP HASIL BELAJAR AKUNTANSI DITINJAU DARI MOTIVASI BELAJAR SISWA - Wiyono Wiyono (Universitas Sebelas Maret Surakarta, 2012)
The aims of the research are to find out: (1) The Effect of concept mapping technique and gaming technique toward the student achievement in accounting subject matter; (2) The Effect of high students's motivation and low students's motivation toward the student achievement in accounting subject matter; (3) The interaction effect between the instructional technique and students's motivation toward the st ident achievement in accounting subject matter.This study is a quantitative research with quasi experimental method. The research begin October 2010 to March 2011. Population of the study are all the eleventh year students of state senior high school 1 for social study major in Surakarta. The research sample are selected with simple random sampling technique. The sample consist of XI IPS 2 (25 students) for concept mapping technique treatment and XI IPS 2 (26 students) for gaming technique treatment.The instruments used to gather dafa for the study consist of documents, written test with essay form, performance test, and questionnaire for students' motivation. Writen test with essay form and questionnaire for students' motivation has been tested who know the proper of instruments. The result of try out test is analyzed with content validity test, item validity test, and reliability test. Item validity test and reliability test were examined using software SPSS.The technique of data analysis are descriptive statistic analysis and inferensial statistic analyses with use software MINITAB. Descriptive statistic analysis is used to divisions of students' motivation in ciass and describe about student achievement in accounting. Inferensial statistic analysis is used to test hypothesis for this research was two path variance analysis. The prerequiste anlysis test consists of normaly test and homogenity variance test. The normality test was done using anderson darling and homogenity variance test was done using F's test.Based on the result of analysis data was concluded: (1) There is a significant effect of concept mapping technique and gaming technique toward the student achievement in accounting subject matter (Fobs > Ftable = 7.94 > 4.06) at 5% level of significant; (2) There is a significant effect of high students' motivation and low students' motivation toward the student achievement in accounting subject matter (Fobs > Ftable = 449.19 > 4.06) at 5% level of significant at 5% level of significant; (3) There is a significant interaction effect between the instructional technique and students' motivation toward the student achievement in accounting subject matter (Fobs > Ftable = 22.47 > 4.06) at 5% level of significant.Key words: Concept mapping technique, gaming technique, students' motivation, student achievement in accounting subject matter.